A Higher Proportion of Iron-Rich Leafy Vegetables in a Typical Burkinabe Maize Meal Does Not Increase the Amount of Iron Absorbed in Young Women1–3. Issue 9 (16th July 2014) - Cercamondi, Colin I.; Icard-Vernière, Christèle; Egli, Ines M.; Vernay, Marlène; Hama, Fatoumata; Brouwer, Inge D.; Zeder, Christophe; Berger, Jacques; Hurrell, Richard F.; Mouquet-Rivier, Claire
Abstract: Food-to-food fortification can be a promising approach to improve the low dietary iron intake and bioavailability from monotonous diets based on a small number of staple plant foods. In Burkina Faso, the common diet consists of a thick, cereal-based paste consumed with sauces composed of mainly green leaves, such as amaranth and jute leaves. Increasing the quantity of leaves in the sauces substantially increases their iron concentration. To evaluate whether increasing the quantity of leaves in sauces would provide additional bioavailable iron, an iron absorption study in 18 young women was conducted in Zurich, Switzerland. Burkinabe composite test meals consisting of the maize paste tô accompanied by an iron-improved amaranth sauce, an iron-improved jute sauce, or a traditional amaranth sauce were provided as multiple meals twice a day for 2 consecutive days. Iron absorption was measured as erythrocyte incorporation of stable iron isotopes. Mean fractional iron absorption from maize paste consumed with an iron-improved amaranth sauce (4.9%) did not differ from the same meal consumed with an iron-improved jute sauce (4.9%; P = 0.9), resulting in a similar quantity of total iron absorbed (679 vs. 578 μg; P = 0.3). Mean fractional iron absorption from maize paste accompanied by a traditional amaranth sauce (7.4%) was significantly higher than that from the other 2 meal types ( P < 0.05), but the quantity of total iron absorbed was similar (591 μg ; P = 0.4 and 0.7, respectively). A food-to-food fortification approach based on an increase in leafy vegetables does not provide additional bioavailable iron, presumably due to the high phenolic compound concentration of the leaves tested. Alternative measures, such as adding iron absorption enhancers to the sauces, need to be investigated to improve iron nutrition from Burkinabe maize meals.